How do you solve -(x+2)-2x=-2(x+1)?
2 Answers
Explanation:
Firstly, you need to get the
-x - 2 = -2 (x + 1) + 2x
which can be simplified by expanding the brackets then simplifying
-x - 2 = -2
which in turn can be also simplified by adding 2 to both sides, giving you
-x = 0
which is the same as
x = 0
Hopefully this was helpful...
See the entire solution process below:
Explanation:
First, expand the terms within parenthesis. Take special care to ensure you manage the signs of the individual terms correctly:
We can next group and combine like terms on the left side of the equation:
Now, we can add